Exploring registered nurses’ experiences and perceptions of nurse manager leadership and its impact on work engagement: A qualitative study set in Saudi Arabia - Amal Alluhaybi; Kim Usher; Joanne Durkin; Amanda Wilson (PLoS ONE, 2026)
Aim To explore nurses’ perceptions of the impact of nurse managers’ leadership practices on work engagement. Design A qualitative descriptive study. Method Thirteen (13) registered nurses were recruited from different departments in four referral hospitals in Saudi Arabia. Data were collected using semi-structured interviews, and thematic analysis was conducted using NVivo-12 software. The findings were reported following the COREQ checklist. Results Key themes included the impact of (1) fair, equitable, and culturally competent nurse managers, (2) effective communication styles by nurse managers, and (3) supportive and collaborative nurse managers. These elements have a positive impact on the level of nurse work engagement. Conclusion Nurse managers’ leadership and interaction with their staff can impact nurses’ sense of engagement in their work. Engaged nurses demonstrate higher levels of motivation, job satisfaction, and commitment, which can enhance patient care quality and workplace efficiency. The findings emphasise the importance of key leadership qualities, including cultural competence, effective communication, and supportive leadership, in fostering nurse engagement. These competencies not only improve staff motivation but also contribute to better patient outcomes. Future research should further explore the intersection of leadership practices and diverse cultural contexts to deepen the understanding of how culturally responsive leadership can enhance nurse engagement across various settings. Implications To enhance nurse engagement and patient care outcomes, nurse managers should develop their leadership skills, particularly in fairness, cultural competence, and communication. Nursing policymakers should prioritise these competencies in leadership training to foster a supportive workplace. Incorporating cultural competence into leadership training policies will help retain a motivated and diverse nursing workforce. Future research should explore interventions that further develop these leadership skills to improve nurse engagement and patient outcomes.